The Spacial Distribution and Time Variations in Physico-chemical Parameters of Groundwater at Khartoum Area- between two Niles–Sudan - Ahmed, Braa Abdelwdood Ali; Elsheikh, Abdalla Eltom Mohamed; Zeinelabdein, Khalid Abderahman Elsayed (European Journal of Applied Sciences, 2025)
The study area occupied the Khartoum area at the confluence of the Blue and White Niles. The main groundwater-bearing formations in the study area are the Gezira and Sandstone sedimentary Formations. The main objective of the current investigation is to determine the correlation between physicochemical properties and their spatial distribution in different time intervals. The methods of investigations were based on the acquired hydro-chemical data and on their analytical results. The average of PH values in the two aquifers is in continuous changes from alkaline toward acidic water type. The dominant water samples were classified as hard and moderately hard. The average TDS value is about 394 mg/l for Gezira aquifer and about 373 mg/l for Sandstone aquifer. The anionic and cationic composition shows that the Bicarbonate (HCO3-1), Sodium (Na+1), Sulphate (SO4-2) and Chloride (Cl-1) ions are the highest concentrations in the two aquifers. The correlation matrix of 15 variables shows significant impact of period variations. (HCO3-1) - (Ca++) and (HCO3-1) - (Na+) are the dominant water facies. The majority of samples fall in rock dominance, the dissolution of carbonate and silicate minerals are the dominant controlling factors of the groundwater chemistry. The chlorine-alkali index (CAI), give an indication of the occurrence of exchange between Ca2+ and Mg2+ ions in water and Na+1 and K+1 ions in the host rocks. The Ammonia and Nitrate average values in both aquifers are increased with time as indicator of pollution, in which the Gezira aquifer is mostly affected.